STUDI KEKASARAN PERMUKAAN RESIN KOMPOSIT NANOFILLER SETELAH PERENDAMAN DALAM SEDUHAN KOPI ARABIKA GAYO - Viona Diansari; Suzanna Sungkar; Cut Rini Hardiyanti (Journal of Syiah Kuala Dentistry Society, 2019)
Nanofilled composite resin has a filler particles in the nanometer range, so that can improve physical properties and enhance esthetics. Surface roughness of nanofilled composite resin are measured fromthe condition of material that can absorp the solution. Water absorption is determined by solution ofimmersion. Gayo arabica coffee is one of immersion that can be absorbed by nanofilled composite resinand contain of acids. The aim of this study is to determine the surface roughness value of nanofilledcomposite resin after immersion in gayo arabica coffee. There were 10 specimens of nanofilledcomposite resin (merk Filtek Z350 XT) with cylinder size (d=10 mm; t=2 mm). Each specimen wasinitially immersed in distilled water at 37oC for 24 hours and its initial roughness was measured usingsurface roughness tester. Then, specimens were immersed in gayo arabica coffee at 55C for 4 days.After immersion, all specimens were measured using surface roughness tester to determine the finalroughness. The data was analyzed using paired t-test with significant value is p0.05. The resultshowed there was significant difference of surface roughness before and after immersion in gayoarabica coffee. The conclusion of this study there was increased in surface roughness nanofilledcomposite resin after immersion in gayo arabica coffee.Keywords : nanofilled composite resin, surface roughness, gayo arabica coffee.